AI4RD: policy, technology, and applications - DONG Hao; WEI Kai (大数据, 2025)
Artificial intelligence for research and development (AI4RD) has evolved into a highly interdisciplinary field, integrating knowledge and methods from diverse disciplines with broad applications in scientific research and industrial development. This paper will delve into the origins, development, and future trends of AI4RD. First, we will define the concept of AI4RD, clarifying its scope and core characteristics. Next, we will analyze the strategic policies of major global economies in this area. Following that, we will introduce the key technologies of AI4RD and examine its practical outcomes in different research fields. Finally, we will explore the future evolution of AI4RD. We believe that AI4RD will profoundly transform scientific discovery methods, reshape technological innovation processes, and provide significant support in addressing major challenges faced by human society.